Outbreak of feline infectious peritonitis (FIP) in shelter-housed cats: molecular analysis of the feline coronavirus S1/S2 cleavage site consistent with a ‘circulating virulent–avirulent theory’ of FIP pathogenesis - Eleni A Healey; Nicole M Andre; Andrew D Miller; Gary R Whittaker; Elizabeth A Berliner (Journal of Feline Medicine and Surgery Open Reports, 2022)
Case series summary This case series describes three shelter-housed cats concurrently diagnosed with feline infectious peritonitis (FIP). The cats were from a cohort of seven surrendered from the site of a house fire. The three cats presented with mild upper respiratory signs. Within 10 days they clinically declined: progressive signs included pyrexia, icterus, lethargy, anorexia and cavitary effusions. Necropsy followed by histopathology and immunohistochemistry confirmed a diagnosis of FIP in all three. Molecular analysis of the causative feline coronavirus (FCoV) revealed varied amino acid alterations in the spike gene both between cats and between sample types in individual cats. A fourth cat from the cohort remained healthy in the shelter but succumbed to FIP 6 weeks post-adoption. Relevance and novel information This case series places FCoV genetic sequences in the context of clinical signs in a small shelter outbreak. Each of the three cats concurrently developed a slightly different clinical presentation. PCR amplification and genetic sequencing revealed that two cats shared an S1/S2 cleavage site mutation (R790S) previously described to be associated with the development of FIP; one of the cats had an additional S1/S2 cleavage site mutation (R793S). The third cat had a single, identical S1/S2 point mutation (R790G) unique from the other two cats; the R790G mutation has not been previously reported. This case series provides interesting data on point mutations associated with the development of FIP and provides support for a ‘circulating virulent–avirulent theory’ of FIP pathogenesis in a small shelter outbreak.